(untitled) (Northern University Journal of Law, 2014)
Law, whether divine or manmade, is always for the well-being of the human beings. In other words, laws are ultimately related to life experiences which are not a monopoly of the theologians only.1 As the society is not any constant phenomenon, it inevitably changes every moment. As a result laws are needed to be changed in compliance with the changing demands of the society. In Islamic Legal System as well the iron fist of taqlid (the doctrine of imitation) had to give way to ijtihad (meaning independent and free exercise of intellect to interpret interpretation of Islamic laws). It is always open for and permitted to, the thinkers, lawmakers and the rulers who are entrusted to apply shariah in society. In this short commentary I intend to address a particular issue relating to the orphaned childrens inheritance right. This is an extremely practical anomaly of the Doctrine of Representation usually escaping our notice. DOI: http://dx.doi.org/10.3329/nujl.v1i0.18521 Northern University Journal of Law Vol.1 2010: 7-13